The Principal’s Role as A Supervisor in Improving Teacher Performance at SDIT Baitul Jannah Bandar Lampung Performance - Budi Suhati Lestari; Sowiyah; Dedy Hermanto Karwan (Publisher Cv. Inara, 2020)
Abstrak: Supervising is a cooperative service. Supervising can be understood to be helpful in two directions as it is applied. In other words, the supervised instructor and the supervisor themselves are promoted and reorganized so that, in turn, teachers may become professionals. This study was conducted to reveal: 1) The role of the Principal in Learning Preparation to enhance teacher success as an Instructional Supervisor. 2) The role of the Principal in integrating learning to increase success as an Instructional Supervisor. 3) The role of the Principal in Learning Assessment to enhance teacher efficiency as an Instructional Supervisor. The role of the Principal as a supervisor in improving teacher performance at SDIT BaitulJannah has been well achieved from the results of the study but needs to be improved again. The Principal has done his best to guide, direct, design, inspire, assess, and maintain good ties from within and outside the school. However, there were some hurdles, including the short-term supervision of all teachers. While support is required, namely the teachers' willingness to obtain guidance from SDIT Principal BaitulJannah, active involvement of students in school activities, help from superiors, and good relations between school members.